Les fondements institutionnels du processus décisionnel de la Cour supérieure et de la Commission des affaires sociales - Morel, François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
Administrative justice implies a speedy resolution of a large number of cases, employing methods that are more informal, more accessible, and less costly than those which are inherent in the functioning of the traditional court system. Given these fundamental differences, the jurist can ask whether administrative tribunals, on the one hand, and traditional courts, on the other, arrive at similar judicial resolutions to similar legal problems. More pointedly, « Is administrative justice comparable in quality to that rendered by the traditional civil courts ? » This problem is addressed here through a methodical examination of the decision-making process, as employed by the Superior court of Quebec, and the Commission des affaires sociales, to give effect over the medium term (1976-1984) to two legal rules. A corpus of pertinent judgements and decisions is studied, with a view to discover how these rulings reflect the institutional and procedural differences underlying the decision-making process of the Superior court and of the Commission des affaires sociales. It is assumed that this process is the same for both institutions, and can be artificially fragmented and examined, in the light of the selected judgements and decisions. The result is a step-by-step, comparative commentary on the quality of justice as rendered by a traditional civil court and an administrative tribunal.